Antibiofilm and antifungal activities of medium‐chain fatty acids against Candida albicans via mimicking of the quorum‐sensing molecule farnesol. Issue 4 (30th November 2020) - Lee, Jin‐Hyung; Kim, Yong‐Guy; Khadke, Sagar Kiran; Lee, Jintae
Summary: Candida biofilms are tolerant to conventional antifungal therapeutics and the host immune system. The transition of yeast cells to hyphae is considered a key step in C. albicans biofilm development, and this transition is inhibited by the quorum‐sensing molecule farnesol. We hypothesized that fatty acids mimicking farnesol might influence hyphal and biofilm formation by C. albicans . Among 31 saturated and unsaturated fatty acids, six medium‐chain saturated fatty acids, that is, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid and lauric acid, effectively inhibited C. albicans biofilm formation by more than 75% at 2 µg ml −1 with MICs in the range 100–200 µg ml −1 . These six fatty acids at 2 µg ml −1 and farnesol at 100 µg ml −1 inhibited hyphal growth and cell aggregation. The addition of fatty acids to C. albicans cultures decreased the productions of farnesol and sterols. Furthermore, down‐regulation of several hyphal and biofilm‐related genes caused by heptanoic or nonanoic acid closely resembled the changes caused by farnesol. In addition, nonanoic acid, the most effective compound diminished C. albicans virulence in a Caenorhabditis elegans model. Our results suggest that medium‐chain fatty acids inhibit more effectively hyphal growth and biofilm formation than farnesol. Abstract : We demonstrate that medium‐chain fatty acids mimic the quorum‐sensing molecule farnesol. Six sets of evidence, that is, (i) structural similarities, (ii) inhibition of hyphal growth, (iii) inhibition of biofilm formation, (iv) inhibition of farnesol production, (v) inhibition of sterol production, and (vi) effects on gene expressions, which showed medium‐chain fatty acids interfere with farnesol signaling and that their antibiofilm and antivirulence activities are superior to that of farnesol. Our findings show that fatty acids found in prokaryotes and eukaryotes might interfere with fungal communication and that medium‐chain fatty acids might be used as developmental starting points for the design of potent antibiofilm and antifungal agents against fungal Candida species.